Predictive nomogram for postoperative lower-limb deep vein thrombosis in patients undergoing endoscopic endonasal surgery during hospitalization: a retrospective cohort study - Hai Peng; Ruofei Yuan; Zhe Zhang; Ying Wang; Xingchao Wang; Bo Wang; Peng Li (Scientific Reports)
Abstract Deep vein thrombosis (DVT) in patients undergoing endoscopic endonasal surgery remains underexplored, despite its potential impact on postoperative recovery. This study aimed to develop and validate a predictive nomogram for assessing the risk of lower-limb DVT in such patients without chemoprophylaxis. A retrospective analysis was conducted on 935 patients with postoperative lower-limb vein ultrasonography. Clinical data, including potential risk factors, were used to construct a predictive model via multivariate logistic regression analysis. The resulting nomogram was validated using an independent cohort and evaluated through concordance index (C-index), calibration plots, and decision curve analysis. The incidence of postoperative DVT was 28.9%, with most cases being distal (27.2%). Significant predictors included older age, intraoperative bleeding, female gender, prolonged surgery duration, elevated postoperative APTT and D-dimer levels, and disturbance of consciousness. The nomogram demonstrated good predictive performance, with C-index values of 0.81 in the training cohort and 0.75 in the validation cohort. Calibration and decision curve analyses confirmed the model’s clinical applicability. This nomogram offers a practical tool for individualized DVT risk assessment in patients undergoing endoscopic endonasal surgery, facilitating more targeted prophylactic measures.